Combination of a therapeutic cancer vaccine targeting the endogenous retroviral envelope protein ERVMER34-1 with immune-oncology agents facilitates expansion of neoepitope-specific T cells and promotes tumor control - Renee N Donahue; Jeffrey Schlom; James L Gulley; Claudia Palena; Duane H Hamilton; Masafumi Iida; Maria del Mar Maldonado; Maria Gracia-Hernandez; Loc Huu Le (Journal for ImmunoTherapy of Cancer)
Background Endogenous retroviruses (ERVs) are remnants of retrovirus germline infections that occurred over the course of evolution and constitute between 5% and 8% of the human genome. While ERVs tend to be epigenetically silenced in normal adult human tissues, they are often overexpressed in carcinomas and may represent novel immunotherapeutic targets. This study characterizes the ERV envelope protein ERVMER34-1 as a target for a therapeutic cancer vaccine.Methods The expression of ERVMER34-1 in multiple healthy adult and cancer tissues was assessed, as was its immunogenicity, to ascertain whether specific T cells could lyse human carcinoma cell lines expressing ERVMER34-1. Furthermore, the ability of a rationally designed ERVMER34-1-targeted therapeutic vaccine to induce tumor clearance in two murine carcinoma models expressing ERVMER34-1 was examined either as a monotherapy or in combination with anti-programmed cell death protein-1/programmed death-ligand 1 monoclonal antibody (mAb) or the interleukin-15 superagonist N-803.Results The ERVMER34-1 protein was shown to be overexpressed in 232/376 of human carcinomas analyzed while being absent in most healthy adult tissues. High levels of ERVMER34-1 RNA expression associate with decreased survival in uveal melanoma, adenoid cystic, and head and neck carcinomas. ERVMER34-1-specific T cells were detected in peripheral blood mononuclear cells (PBMCs) of patients with cancer but not healthy donors following an overnight stimulation. However, reactive T cells are readily expanded from both healthy donor and patient with cancer PBMCs following a 7- day in vitro stimulation. Furthermore, ERVMER34-1-specific T cells selectively kill human carcinoma cell lines expressing ERVMER34-1. A novel, rationally designed, therapeutic cancer vaccine targeting ERVMER34-1 mediated tumor control in established syngeneic murine tumors expressing the full-length ERVMER34-1 protein. When combined with checkpoint blockade, the vaccine promoted expansion of neoepitope-reactive T cells whose function was further enhanced when combined with N-803. This expansion of neoepitope-reactive T cells was associated with tumor control.Conclusions This study reveals the potential of a vaccine that targets the retroviral envelope protein ERVMER34-1 and supports its continued development toward clinical testing as a new class of therapeutic cancer vaccine.